KOLABORASI STAKEHOLDER DALAM PENGEMBANGAN WISATA KAMPUNG BLEKOK DI KABUPATEN SITUBONDO - Desi Anjarwati; Vita Novianti; Dini Noor Aini (ACTON, 2026)
Kampung Blekok Tourism in Situbondo Regency is a conservation-based tourist destination that holds great potential for development, focusing on environmental preservation and the mangrove ecosystem. However, the development of the area faces various challenges, such as a decline in tourist visits, a lack of coordination among stakeholders, an unoptimized management institutional framework, and a lack of active participation from various parties. This study aims to analyze the stakeholder collaboration process in the development of Kampung Blekok Tourism in Situbondo Regency. The research employs a qualitative method with a descriptive approach, collecting data through interviews, observation, and documentation. Informants were selected using a purposive sampling technique, encompassing elements of government, the private sector, academics, the community, and the media. Data analysis used an interactive model including data reduction, data display, and conclusion drawing. The results of the study show that stakeholder collaboration involves five elements within the pentahelix model, namely government, private sector, academics, community, and media, which is manifested through environmental conservation activities, tourism promotion, community empowerment, Corporate Social Responsibility (CSR) programs, and stakeholder discussion forums. Supporting factors for collaboration include a shared awareness of the importance of environmental preservation, local government support, community involvement, and economic benefits felt by the local community. However, the collaboration has not run optimally due to the absence of a formal management institution, weak coordination and communication among stakeholders, and unclear division of roles. Consequently, stakeholder collaboration in the development of Kampung Blekok Tourism is at an evolving stage, necessitating institutional strengthening, enhanced coordination, and shared commitment to realize sustainable tourism development. Key Words: Stakeholder Collaboration, Pentahelix, Development of Kampung Blekok Tourism.